STRUCTURAL ELUCIDATION OF SECONDARY METABOLITES IN SPONGE (Callyspongia pseudoreticulata) WITH N-HEXANE EXTRACT - M. Nurdin; Hanapi Usman; Ambo Ala; Baharuddin - (PROSIDING SEMINAR KIMIA, 2015)
Sponge is one of marine that have high bioactivity and contain secondary metabobolite compaund which can be used as antibiotic and medicine. Terpenoid compound derivatives have been successfully isolated from sponge Callyspongia pseudoretilulata by a a method in which the n-hexane extract weighting 11.28 g was fractionated using vacuum column chromatography with a non-polar eluent, n-hexane. The polarity of this eluent was improved by ethyl acetic resulting in fairly polar eluent, methanol. Total 27 fractions were obtained and one of the compounds from n-hexane extract was structurally elucidated by NMR spectroscopy and two dimensions of homonuclear and heteronuclear (1H, 13C, DEPT, H-H COSY, HMQC, and HMBC). The identified compound was a hydrocarbon (1-ethyl cyclo hex cosana-1-amin) thatindicated LC50 of 60.58 against A. salina and has a great potential as antitumor or anticancer.